(untitled) (Journal of Architectural Design, 2023)
Tropical kitchen is a culinary space that draws inspiration from tropical regions, incorporating flavors, ingredients, and design elements associated with tropical climates. The study assessed tropical kitchen construction: assessing the prospects and challenges. Constructing kitchens in tropical regions requires specific considerations due to the unique climatic challenges posed by high temperatures and humidity. The selection of appropriate building materials is a fundamental aspect of tropical kitchen construction. Locally sourced, weather-resistant materials such as hardwoods, bamboo, and treated tropical hardwoods are recommended for their ability to withstand the adverse effects of high humidity and heat. Revealed in this study one significant challenge faced by tropical kitchens is the high humidity prevalent in tropical regions. The moisture in the air can lead to issues such as mold growth, wood rot, and damage to appliances. On this basis the study concluded that while opportunities for sustainable practices and cultural integration exist, the complexities of high humidity, extreme weather events, and diverse cultural preferences demand innovative solutions. Integrating eco-friendly materials, resilient design, and community engagement emerges as essential for creating kitchens that are not only structurally sound but also culturally sensitive. One of the recommendations made was that architect should ensure that they prioritize climateresponsive design elements such as natural ventilation, shading, and insulation to mitigate the impact of high temperatures and humidity on kitchen structures.